MDM2 inhibitor induces apoptosis in colon cancer cells through activation of the CHOP-DR5 pathway, independent of p53 phenotype - Lu, Manman; Ren, Yingli; Feng, Sijia; Wang, Shenggen; Xia, Weiyue; Gu, Baoru; Shen, Yuhou; Yue, Aimin; Li, Na; Zhang, Yongxi; Zhong, Jiateng (Frontiers in Pharmacology, 2025)
IntroductionMurine double minute 2 (MDM2), a key negative regulator of p53, forms a feedback loop with p53 to drive tumor progression, including colorectal cancer. Nutlin-3a, an MDM2 inhibitor, induces apoptosis in wild-type p53 tumors, but its effects on p53-mutated cancers and potential p53-independent apoptotic mechanisms remain unclear.MethodsWe investigated Nutlin-3a's effects on colon cancer cells with varying p53 phenotypes. Endoplasmic reticulum (ER) stress-associated CHOP was detected and knocked down to explore mechanisms. In vitro and in vivo experiments assessed Nutlin-3a's synergy with 5-fluorouracil and TRAIL.ResultsNutlin-3a activated caspase-8-dependent extrinsic apoptosis in colon cancer cells via DR5 upregulation, independent of p53 status. ER stress and CHOP activation mediated DR5 induction, driven by calcium release. Combined Nutlin-3a treatment enhanced sensitivity to 5-fluorouracil and TRAIL in vitro and in vivo through caspase-8 pathway activation.DiscussionThese findings reveal a novel p53-independent apoptotic mechanism of Nutlin-3a involving ER stress and death receptor signaling. This pathway highlights Nutlin-3a's potential as an adjuvant therapy for colon cancer, even in p53-mutated tumors, by enhancing chemotherapeutic efficacy through extrinsic apoptosis.